Ground response of rolling dynamic compaction—a finite element modelling approach - Bradley, A. C.; Jaksa, M. B.; Kuo, Y. L. (Frontiers in Built Environment, 2024)
Rolling dynamic compaction (RDC) technology utilises a heavy non-circular module (impact roller) to compact the underlying soil dynamically. The stresses imparted to the soil through this technique and the resulting vibrations, have been the subject of investigation in the field. A finite element (FE) model predicting the settlement and densification of a coarse-grained fill material subject to RDC with a BH-1300 4-sided 8 tonne impact roller has been shown to provide good agreement with that observed in the field. This paper presents estimates using the developed FE model for the peak particle velocity and acceleration, and the maximum stresses applied through each impact upon a coarse-grained soil. Distributions of the results and their empirical formulae are presented herein.